Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Prove that $$\frac{1} {(1-p)^2} = \sum_{x=2}^\infty x^2p^{x-2} \, .$$

The professor suggested that we start by taking the derivative of $$\frac{1} {(1-p)^2} = \sum_{x=1}^\infty xp^{x-1} \, .$$

So I have tried that, and then broken the derivative up into $$ \sum_{x=2}^\infty x^2p^{x-2} \, - \sum_{x=2}^\infty xp^{x-2} \, .$$ by taking apart x(x-1)

but I can't get any further and I am extremely confused.

share|improve this question
1  
You should consider adding some thoughts about your current approach to the problem. Without knowing how you're trying to do this, we don't have any idea what background you have or how best to help you. –  Muphrid Feb 4 '13 at 5:53
add comment

2 Answers

From $$\frac{1}{(1-p)^2} = \sum_{x \geq 1} x \cdot p^{x-1} \tag{1} $$ you obtain by differentiating (with respect to $p$):

$$\begin{align} \frac{2}{(1-p)^3} &= \sum_{x \geq 2} x \cdot (x-1) \cdot p^{x-2} = \sum_{x \geq 2} x^2 \cdot p^{x-2} - \underbrace{\sum_{x \geq 2} x \cdot p^{x-2}}_{\frac{1}{p} \cdot \sum_{x \geq 2} x \cdot p^{x-1}} \\ &= \sum_{x \geq 2} x^2 \cdot p^{x-2} - \frac{1}{p} \cdot \left( \sum_{x \geq 1} x \cdot p^{x-1} -1 \right) \\ &\stackrel{(1)}{=} \sum_{x \geq 2} x^2 \cdot p^{x-2} - \frac{1}{p} \cdot \left( \frac{1}{(1-p)^2} -1 \right) \end{align}$$

Hence

$$\sum_{x \geq 2} x^2 \cdot p^{x-2} = \frac{p^2-3p+4}{(1-p)^3}$$

(There has to be a mistake or typo in your claim, because if the equality $$\sum_{x \geq 2} x^2 \cdot p^{x-2} =\frac{1}{(1-p)^2}$$ holds, this would imply $$ 0 = \frac{1}{(1-p)^2} - \frac{1}{(1-p)^2} = \sum_{x \geq 2} x^2 \cdot p^{x-2} - \sum_{x \geq 1} x \cdot p^{x-1} = \sum_{x \geq 0} \underbrace{((x+2)^2-(x+1))}_{\geq 0} \cdot \underbrace{p^x}_{\geq 0}$$ by using (1). And this can only hold iff $$(x+2)^2-(x+1) = 0$$ for all $x \in \mathbb{N}$. And this is clearly not fulfilled.)

share|improve this answer
add comment

For $\,|p|<1\,$ it is well known that

$$f(p):=\frac{1}{1-p}=\sum_{x=0}^\infty p^x\Longrightarrow f'(p)=\frac{1}{(1-p)^2}=\sum_{x=1}^\infty xp^{k-1}$$

So in fact your first equality's right hand must begin from $\,x=1\,$ and with $\,x\,$ but not squared...check this.

share|improve this answer
    
That's exactly what Kathleen wrote in the second equation. (But as you can see in my answer, I would also say that there is some mistake in the claim.) –  saz Feb 7 '13 at 13:41
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.